The Effect of Leisurely Walking Therapy on Blood Pressure Changes in Elderly Patients with Hypertension - marrita sari (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Hypertension is one of the most common chronic diseases among older adults and a major risk factor for cardiovascular complications. Non-pharmacological interventions, including physical activity, are recommended to support blood pressure control. Leisurely walking is a simple, safe, and low-cost form of aerobic exercise that may help reduce blood pressure in older adults with hypertension. Method: This study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. A total of 30 older adults with hypertension were recruited and divided into an intervention group (n=15) and a control group (n=15). The intervention group participated in a leisurely walking program for 15–30 minutes per session, 3–5 times per week, for 4 weeks, while the control group received routine care. Blood pressure was measured before and after the intervention. Data were analyzed using paired and independent sample statistical tests with a significance level of p<0.05. Results: The intervention group demonstrated a significant reduction in mean systolic blood pressure from 154.67±8.21 mmHg to 142.13±7.45 mmHg and diastolic blood pressure from 95.33±5.16 mmHg to 88.20±4.52 mmHg (p<0.05). In contrast, the control group showed no significant changes in blood pressure. Comparative analysis revealed that the reduction in systolic and diastolic blood pressure was significantly greater in the intervention group than in the control group (p<0.05). Conclusion: Leisurely walking is effective in reducing systolic and diastolic blood pressure among older adults with hypertension. This intervention can be recommended as a safe, simple, and cost-effective non-pharmacological strategy for hypertension management in primary healthcare settings.